Educational technology for pregnant women on rapid HIV testing: validation study - Sousa, Mariana Matias de; Cardoso, Ana Cláudia Paiva Cardoso Paiva; Feitosa, Bruno Raphael da Silva; Silva, Marlucilena Pinheiro da; Teixeira, Elizabeth; Pena, Francineide Pereira da Silva; Nemer, Camila Rodrigues Barbosa (Revista de Enfermagem da UFPI, 2024)
Objective: To describe the process of validating a booklet for pregnant women on the rapid test for the Human Immunodeficiency Virus. Method: Methodological research with a quantitative approach, with an emphasis on content and appearance validation. Data collection took place between January and August 2020, with the application of two online questionnaires, one for 14 health judges and the other for four judges from other areas. Descriptive statistics were used to obtain the Content Validity Index (minimum 0.7) and the Suitability Assessment of Materials score (minimum ten points). Results: The Content Validity Index was 0.8 and the SAM score was 25.25. Conclusion: The booklet was considered adequate in terms of content and appearance, and can mediate educational actions with pregnant women on rapid HIV testing.